(untitled) (Research, Society and Development, 2022)
The infant mortality rate (IMR) represents one of the most relevant health indicators, from which it is possible to assess the weaknesses of populations. To analyze the epidemiology of IMR between the years 2016 to 2020 in a national, regional, state panorama compared to local data. An ecological and retrospective study of a time series was carried out and the vital statistics of deaths under one year available in the SIM were adopted. The data were systematized in Biostat, performing the t Test. There is a slight decline in the country, from 12.7 deaths per thousand LBs in 2016 to 11.5 deaths per thousand LBs in 2020. This downward trend remained present in the Northeast (NE) region (14.4 to 12, 9), Piauí (16.2 to 13.7) and Parnaíba (15.0 to 12.6), although they remain above the national average. Comparing Parnaíba with Brazil, there was a statistically significant difference. Conditions originating in the perinatal period were the most representative, in the national scenario (47.5%), regional (60.6%), state (47.5%) and local (61.9%). More than half of deaths could be avoided if adequate measures regarding care for women during pregnancy and childbirth were present. There was significance in the comparisons between the death avoidability indices for Brazil and the NE and those for Parnaíba. Of the deaths not investigated, 18.3% in Brazil, 21% in the NE, 21.5% in Piauí and 14.2% in Parnaíba. There is a need to intensify public policies and investment institutions in the qualification of assistance to the mother-father-child triad, especially in Primary Health Care.